Integrative Pan-Cancer Analysis Confirmed that FCGR3A is a Candidate Biomarker Associated With Tumor Immunity - Li, Lilin; Huang, Zijian; Du, Kunpeng; Liu, Xiang; Li, Chunhui; Wang, Duanyu; Zhang, Yangfeng; Wang, Changqian; Li, Jiqiang (Frontiers in Pharmacology, 2022)
Background: Fc gamma receptors 3A (FCGR3A) encodes a receptor for the Fc portion of immunoglobulin G, which plays a significant role in the immune response. However, the role of FCGR3A in cancers remains unclear. This study aimed to visualize the prognostic landscape of FCGR3A in pan-cancer and investigate the relationship between FCGR3A expression and tumor microenvironment. Method: Based on the TCGA database, GTEx database, and GDSC database, we analyzed the expression of FCGR3A in pan-cancers and adjacent normal tissues and its relationship with prognosis, immune cells infiltration, immune-related genes, DNA mismatch repair (MMR) genes, DNA methylation, and drugs sensitivity. The gene alteration frequency of FCGR3A was acquired on the cBioportal website. Moreover, we constructed PPI networks, performed GO and KEGG analysis to illustrate the function, and signaling pathways of FCGR3A-related genes, and conducted gene set enrichment analysis (GSEA) of FCGR3A to further explore its potential biological functions. Result: The differential analysis results of the publicly available databases showed that FCGR3A was generally highly expressed in pan-cancer. Survival analysis revealed that FCGR3A predominated as a risk prognostic factor in most cancers. Additionally, the expression of FCGR3A was confirmed to be associated with several immune cells infiltration, multiple immune checkpoint genes, and DNA mismatch repair genes expression in generalized carcinoma. We also identified a negative correlation between FCGR3A and DNA methylation levels. Through GO/KEGG and GESA, we found that FCGR3A was involved in many pathologic and physiological processes, and was most closely related to tumor immune-related pathways. Drug sensitivity analysis showed that higher FCGR3A expression predicts a low IC50 value for the vast majority of drugs. Conclusions: FCGR3A may be an immune-oncogenic molecule that correlates with tumor immune infiltration levels and affects drug sensitivity, thus it can be served as a promising biomarker for cancer detection, prognosis, therapeutic design, and follow-up.